2010
DOI: 10.1080/1331677x.2010.11517421
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Tourism Destination Image Concept into Customer-Based Brand Equity For A Tourism Destination

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…A strong perceived quality position is an advantage, which is not easily replaced by competitors (Konecnik&Gartner, 2007;Boo, et al, 2010;Pike, et al, 2010;Ruizzer, 2010;Lin, 2011). In several studies, it is found out that event brand quality has an important role in influencing revisit intention.…”
Section: Event Brand Qualitymentioning
confidence: 99%
“…A strong perceived quality position is an advantage, which is not easily replaced by competitors (Konecnik&Gartner, 2007;Boo, et al, 2010;Pike, et al, 2010;Ruizzer, 2010;Lin, 2011). In several studies, it is found out that event brand quality has an important role in influencing revisit intention.…”
Section: Event Brand Qualitymentioning
confidence: 99%
“…As in the general concept of image, destination image in tourism is expressed as the whole of the potential tourist's belief in, attitude toward, and perception, views and impressions about the destination (Ruzzier, 2010;Gallarza et al, 2002;Gartner, 1994;Hunt, 1975). Early studies found that destination image is an effective factor in the process of the tourist's decision to buy and to select the destination (Dadgostar & Isotalo, 1992;Jenkins 1999;Milman & Pizam, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study, Ruzzier (2010) examined the perspective of the demand in tourism destination phenomenon. The statistical population of study was German and Croatia tourists whose destination was two countries of Germany and Slovenia.…”
Section: Cultural Brand Asset Relationship With Brand Awarenessmentioning
confidence: 99%
“…The results suggest that the concept of the image traditionally represents the most important dimension in the evaluation of one part. However, for a more comprehensive evaluation of tourism destination dimensions, knowledge, quality and loyalty should be added (Ruzzier, 2010). The results of Kladou and Kehagias's (2014) study on evaluation of structural relationship between brand equity dimensions showed that when five dimensions of brand equity and cultural brand equity were combined, the importance of cultural brand asset is revealed for brand equity.…”
Section: Cultural Brand Asset Relationship With Brand Awarenessmentioning
confidence: 99%